Mechanical performance of montmorillonite dispersed jute reinforced composite - Muhammad Hasibul , Hasan; Md. Sazib Mollik, Sazib (2015)
Surface treated jute accomplished by chemical treatments which enhanced the adhesion between polyester resin and modified surface within the composite. Baking time for 6 hours also reduced the moisture content and diminishes the hydrophilic properties of the corchorus olitorius jute fiber. Montmorillonite shell type nanoclay was dispersed 1%, 3% and 5% within the jute fiber polyester matrix to enhance the mechanical performance. Effect of temperature and high humidity were evaluated for this nanoclay filled composite through hydrothermal test for 15 days in the environmental chamber. Environmental degradation was not remarkable due to the exposure of the temperature 80ᴼC and 95% RH for this time period. Ductile properties like yield strength (YS), % of elongation were calculated for two different stoke rate to understand the strain rate effect. 1% addition of nanoclay within the composite shows the better performance in terms of yield, flexural and impact strength while 5% dispersed of nanoclay does not have any beneficial effect within the composite due to the density and non-homogeneous mixture of the clay. Fracture morphology by SEM/ FESEM revealed voids, broken fibers and nano particles within the matrix.